A PEDAGOGICAL DECISION-MAKING IN INTEGRATING INTERACTIVE AUDIO-VISUAL TOOLS INTO VOCABULARY INSTRUCTION: EVIDENCE FROM ENGLISH TEACHERS - Harizah Zafirah; Nyimas Triyana Safitri; Hidayati Hidayati (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
The integration of interactive audio-visual tools into vocabulary instruction involves a series of pedagogical considerations that shape how teachers select, use, modify, and assess digital resources in classroom practice. Therefore, this study aims to examine the process of teachers’ pedagogical decision-making when integrating interactive audio-visual tools into vocabulary instruction. Employing a descriptive qualitative research design, this study collected data through semi-structured interviews with two English teachers, and the data were analyzed using Braun and Clarke’s (2006) thematic analysis approach. The findings revealed four interconnected processes of teachers’ decision-making, including the selection of digital tools aligned with instructional objectives, the integration of interactive tools into vocabulary learning activities, the adaptation of technology use to students’ needs and classroom conditions, and the evaluation of digital tools in supporting vocabulary instruction. Overall, the findings indicate that technology integration in vocabulary instruction is not merely a process of adopting digital tools, but rather a contextual practice shaped by teachers’ ongoing pedagogical decisions and instructional considerations.